2018
DOI: 10.1002/pola.28973
|View full text |Cite
|
Sign up to set email alerts
|

Modulated release from implantable ocular silicone oil tamponade drug reservoirs

Abstract: Complicated cases of retinal detachment can be treated with silicone oil tamponades. There is the potential for silicone oil tamponades to have adjunctive drug releasing behaviour within the eye, however the lipophilic nature of silicone oil limits the number of drugs that are suitable, and drug release from the hydrophobic reservoir is uncontrolled. Here, a radiometric technique was developed to accurately measure drug solubility in silicone oil and measure release into culture media. All‐trans retinoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…A well-established delivery system is the silicone oil (SIO) tamponade which has been used clinically since 1958, usually for eye surgeries such as proliferative vitreoretinopathy (PVR) or retinal detachment/tears. Due to the close proximity to the retina, SIO can be dosed with drugs [61]. Despite its historical use, it is not without its drawbacks; a study showed 17.5% of neovascular AMD patients who underwent macular translocation surgery, followed by a SIO tamponade, went on to develop retinal detachment one month after removal [62] highlighting a need for an improved drug delivery system to the retina.…”
Section: Delivery Of Drugsmentioning
confidence: 99%
“…A well-established delivery system is the silicone oil (SIO) tamponade which has been used clinically since 1958, usually for eye surgeries such as proliferative vitreoretinopathy (PVR) or retinal detachment/tears. Due to the close proximity to the retina, SIO can be dosed with drugs [61]. Despite its historical use, it is not without its drawbacks; a study showed 17.5% of neovascular AMD patients who underwent macular translocation surgery, followed by a SIO tamponade, went on to develop retinal detachment one month after removal [62] highlighting a need for an improved drug delivery system to the retina.…”
Section: Delivery Of Drugsmentioning
confidence: 99%
“…Recently, by chemically modifying the side branches of the polymer chains of SiO, solubility of lipophilic drugs, such as ibuprofen and all‐trans retinoic acid, are significantly enhanced (Cauldbeck et al. , ). This inspires the opportunity of using SiO as an effective reservoir to deliver and sustained release ophthalmic drugs into the eye.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this study is that previous studies on drug release in SiO did not take into account emulsification of SiO (Cauldbeck et al. , ). The pharmacokinetics of drugs is likely to be very different if SiO emulsifies as the total surface area of SiO changes (Lallemand et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations